2005
DOI: 10.1063/1.2048816
|View full text |Cite
|
Sign up to set email alerts
|

Ti O 2 single-crystalline nanorod electrode for quasi-solid-state dye-sensitized solar cells

Abstract: Ti O 2 single-crystalline nanorods are prepared from electrospun fibers which are composed of nanofibrils with an islands-in-a-sea morphology. The mechanical pressure produces each fibril into nanorods which are converted to anatase single crystals after calcination. High-resolution transmission electron microscopy shows that the (001) plane is growing along the longitudinal direction of the rod. In this work, the nanorod electrode provides the efficient photocurrent generation in a quasi-solid-state dye-sensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
107
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(109 citation statements)
references
References 18 publications
0
107
2
Order By: Relevance
“…221 The application of TiO 2 nanorods in DSSCs was demonstrated by Song et al in 2005 as well within a quasi-solid-state dye-sensitized solar cell. 222 The overall conversion efficiency of the TiO 2 nanorods showed 6.2% under 100 mW cm À2 AM 1.5G illumination. 222 Films constructed of oriented one-dimensional nanostructures, such as nanotube (NT) arrays, aligned perpendicular to the collecting substrate can potentially improve the chargecollection efficiency by promoting faster transport and slower recombination.…”
Section: Selected Recent Progressmentioning
confidence: 99%
See 1 more Smart Citation
“…221 The application of TiO 2 nanorods in DSSCs was demonstrated by Song et al in 2005 as well within a quasi-solid-state dye-sensitized solar cell. 222 The overall conversion efficiency of the TiO 2 nanorods showed 6.2% under 100 mW cm À2 AM 1.5G illumination. 222 Films constructed of oriented one-dimensional nanostructures, such as nanotube (NT) arrays, aligned perpendicular to the collecting substrate can potentially improve the chargecollection efficiency by promoting faster transport and slower recombination.…”
Section: Selected Recent Progressmentioning
confidence: 99%
“…222 The overall conversion efficiency of the TiO 2 nanorods showed 6.2% under 100 mW cm À2 AM 1.5G illumination. 222 Films constructed of oriented one-dimensional nanostructures, such as nanotube (NT) arrays, aligned perpendicular to the collecting substrate can potentially improve the chargecollection efficiency by promoting faster transport and slower recombination. A comparison of the electron pathways through nanoparticulate and nanotubular structured TiO 2 is shown in the schematic diagram of Fig.…”
Section: Selected Recent Progressmentioning
confidence: 99%
“…To solve this problem, various pretreatment methods have been developed. [13][14][15] In our previous study, we have shown that a buffer layer could be introduced to improve the adhesion of TiO 2 nanofibers to substrate. 16 Recently, the hot press treatment has also been applied to enhance the adhesion of ZnO nanofibers to the FTO substrate.…”
mentioning
confidence: 99%
“…[461,462] Dye-sensitised solar cells using TiO 2 single-crystalline nanorod electrodes provide efficient photocurrent generation in a quasi-solid-state, with a conversion efficiency of 6.2 % under 100 mWcm À2 . [463] Intercalation of lithium ions in TiO 2 -B nanowires has been carried out without any structural degradation or loss of nanowire morphology. [464] Kim et al [465] have investigated the use of LiMn 2 O 4 nanowires for use as cathodes in lithium batteries.…”
Section: Metal Oxide Nanowiresmentioning
confidence: 99%